Komodifikasi Kewenangan Mahkamah Konstitusi Republik Indonesia melalui Ikhtiar Aktivisme Yudisial - Pradana, Syafa’at Anugrah; Mannan, Khaerul; Annisa, Arini Nur; Prayudi, Prayudi (Amsir Law Journal, 2024)
This paper examines the idea of adding the authority of the Constitutional Court of Republic Indonesia to examine draft laws against the constitution of the basic law with a mechanism called judicial preview. This paper aims to examine the involvement of the judiciary, in this case the Constitutional Court, in the law-making process. This paper is a measure of the involvement of the Constitutional Court in the expansion of authority by examining the constitution against the draft law. The type of research used is library research in the form of normative research using statutory, conceptual, and comparative approaches. The research results obtained found that the existence of the Constitutional Court as the sole interpreter of the constitution shows that the involvement of the Constitutional Court in the law-making process has the potential to improve the quality and constitutionality of the draft law. In terms of functions and main tasks, the Constitutional Court can participate in the law-making process. The Constitutional Court is actually present as a judiciary activism that bases its function as a counter-majoritarian. Therefore, efforts to improve the principle of constitutional supremacy can be realized through input for future improvements. ___ Referensi Buku dengan penulis: Ali, A. (2009). Menguak Teori Hukum (Legal Theory) dan Teori Peradilan (Judicialprudence) termasuk Interpretasi Undang-Undang (Legisprudence). Jakarta: Kencana. Asshiddiqie, J. (2015). Konstitusi Bernegara: Praksis Kenegaraan Bermartabat dan Demokratis. Malang: Setara Press. Atmadja, I. D. G. (2010). Hukum Konstitusi: Problematika Konstitusi Indonesia Sesudah Perubahan UUD 1945. Malang: Setara Press. Black, H. C. (1910). Law Dictionary (p. 1147). St. Paul, Minn.: West Publishing Company. Isra, S. (2010). Menguatnya Model Legislasi Parlementer Dalam Sistem Presidensial Indonesia. Jakarta: Rajawali Pers. Junaidi, M. (2018). Hukum Konstitusi: Pandangan dan Gagasan Modernisasi Negara Hukum. Depok: Rajawali Pers. Saebani, B. A. (2016). Perbandingan Hukum Tata Negara. Bandung: Pustaka Setia. Stone, G. R., Seidman, L. M., Sunstein, C. R., Tushnet, M. V., Karlan, P. S., Huq, A., & Litman, L. M. (2023). Constitutional Law. Boston: Aspen Publishing. Thaib, D., Hamidi, J., & Huda, N. (2011). Teori dan Hukum Konstitusi. Jakarta: RajaGrafindo Persada. Artikel jurnal: Akmal, D. U., Muin, F., & Karsa, P. L. (2020). Prospect of Judicial Preview in the Constitutional Court Based on the Construction of Constitutional Law. Jurnal Cita Hukum, 8(3), 609-626. Ali, M. (2010). Mahkamah Konstitusi dan Penafsiran Hukum yang Progresif. Jurnal Konstitusi, 7(1), 067-090. Ardiansyah, M. K. (2020). Pembaruan Hukum oleh Mahkamah Agung dalam mengisi Kekosongan Hukum Acara Perdata di Indonesia. Jurnal Ilmiah Kebijakan Hukum, 14(2), 361-384. Asy’Ari, S., Hilipito, M. R., & Ali, M. M. (2013). Model dan Implementasi Putusan Mahkamah Konstitusi dalam Pengujian Undang-Undang (Studi Putusan Tahun 2003-2012). Jurnal Konstitusi, 10(4), 675-708. Barroso, L. R. (2019). Countermajoritarian, Representative, and Enlightened: The Roles of Constitutional Courts in Democracies. The American Journal of Comparative Law, 67(1), 109-143. Gaffar, J. M. (2013). Peran Putusan Mahkamah Konstitusi Dalam Perlindungan Hak Asasi Manusia terkait Penyelenggaraan Pemilu. Jurnal Konstitusi, 10(1), 1-32. Hoesein, Z. A. (2012). Pembentukan Hukum dalam Perspektif Pembaruan Hukum. Jurnal Rechts Vinding: Media Pembinaan Hukum Nasional, 1(3), 307-327. Kaimudin, A. (2019). Perlindungan Hukum terhadap Tenaga Kerja Anak Dalam Peraturan Perundang-Undangan di Indonesia. Jurnal Yurispruden, 2(1), 37-50. Manurung, O., Lubis, M. Y., & Affan, I. (2021). Tinjauan Yuridis Pancasila sebagai Staatfundamentalnorm Dalam Menghadapi Kapitalisme Penyelenggaraan Pendidikan Dalam Perspektif Undang-Undang Nomor 12 Tahun 2012. Jurnal Ilmiah METADATA, 3(2), 490-507. Perwira, I. (2016). Refleksi Fenomena Judicialization of Politics pada Politik Hukum Pembentukan Mahkamah Konstitusi dan Putusan Mahkamah Konstitusi. Jurnal Konstitusi, 13(1), 25-47. Pratama, H. M., & Perdana, A. (2021). Judicialization of Politics in Indonesia’s Electoral System Case Study: Judicial Review on Threshold, Balloting Structure, and Simultaneous Election at Constitutional Court. Politik Indonesia: Indonesian Political Science Review, 6(1), 90-110. Prianto, W. (2024). Analisis Hierarki Perundang-Undangan berdasarkan Teori Norma Hukum oleh Hans Kelsen dan Hans Nawiasky. Jurnal Ilmu Sosial dan Pendidikan, 2(1), 08-19. Purwanda, S., & Dewi, M. N. K. (2020). The Effects of Monism and Pluralism on Legal Development of a Nation. Amsir Law Journal, 2(1), 21-26. Qamar, N. (2012). Kewenangan Judicial Review Mahkamah Konstitusi. Jurnal Konstitusi, 1(01), 1-15. Setiadi, W., Sadiawati, D., Meliala, A. J., Bakhtiar, H. S., & Harefa, B. (2021). The Role of Indonesia Constitutional Court Decision in the Process of Establishing the Law: A Case Study in the Process of Establishing the Law on General Elections. J. Legal Ethical & Regul. Isses, 24, 1. Soeroso, F. L. (2016). Pembaruan Hukum Acara Pengujian Peraturan Perundang-Undangan di Bawah Undang-Undang. Kajian, 19(4), 327-347. Soraya, A., Purwanda, S., & Taufik, M. (2023). Perbandingan Pengaturan Hukum Dalam KUHP Lama dan Baru bagi Anak yang menjadi Korban Perdagangan Orang. Dinamika Hukum, 24(2), 250-257. Sukmawan, D. I., & Pratama, S. (2023). Critical Review of the Constitutional Court’s Decision on the Presidential Threshold: Tinjauan Kritis mengenai Putusan Mahkamah Konstitusi tentang Ambang Batas Pencalonan Presiden. Jurnal Konstitusi, 20(4), 556-575. Wicaksono, I. (2019). Optimalisasi Peran Mahkamah Konstitusi Dalam Pembangunan Hukum Nasional dengan Model Preventive Review. Majalah Hukum Nasional, 49(1), 91-116. Yulianto, A. (2020). Judicial Preview sebagai Mekanisme Penakaran Konstitusionalitas Rancangan Undang-Undang. JIL: Journal of Indonesian Law, 1(1), 1-34. Yulida, D., Herawati, R., & Indarja, I. (2021). Perluasan Kewenangan Mahkamah Konstitusi Dalam Menguji Konstitusionalitas Rancangan Undang-Undang Pengesahan Perjanjian Internasional melalui Judicial Preview. Diponegoro Law Journal, 10(2), 342-354. World Wide Web: Luxiana, K.M., (2023). 15 Permohonan Judicial Review UU Dikabulkan MK Sepanjang 2022. Diakses dari laman: https://news.detik.com/berita/d-6736080/15-permohonan-judicial-review-uu-dikabulkan-mk-sepanjang-2022